Inbred mouse strains reveal biomarkers that are pro‐longevity, antilongevity or role switching. Issue 4 (23rd May 2014) - Moeller, Mark; Hirose, Misa; Mueller, Sarah; Roolf, Catrin; Baltrusch, Simone; Ibrahim, Saleh; Junghanss, Christian; Wolkenhauer, Olaf; Jaster, Robert; Köhling, Rüdiger; Kunz, Manfred; Tiedge, Markus; et al.
Summary Traditionally, biomarkers of aging are classified as either pro‐longevity or antilongevity. Using longitudinal data sets from the large‐scale inbred mouse strain study at the Jackson Laboratory Nathan Shock Center, we describe a protocol to identify two kinds of biomarkers: those with prognostic implication for lifespan and those with longitudinal evidence. Our protocol also identifies biomarkers for which, at first sight, there is conflicting evidence. Conflict resolution is possible by postulating a role switch. In these cases, high biomarker values are, for example, antilongevity in early life and pro‐longevity in later life. Role‐switching biomarkers correspond to features that must, for example, be minimized early, but maximized later, for optimal longevity. The clear‐cut pro‐longevity biomarkers we found reflect anti‐inflammatory, anti‐immunosenescent or anti‐anaemic mechanisms, whereas clear‐cut antilongevity biomarkers reflect inflammatory mechanisms. Many highly significant blood biomarkers relate to immune system features, indicating a shift from adaptive to innate processes, whereas most role‐switching biomarkers relate to blood serum features and whole‐body phenotypes. Our biomarker classification approach is applicable to any combination of longitudinal studies with life expectancy data, and it provides insights beyond a simplified scheme of biomarkers for long or short lifespan.